Biocompatibility of Silicone Elastomer Incorporated with Chitosan: Morphology, Mechanical, Biodegradation Assessment and the Potential for Injectable Biomaterials - Rasyida, Amaliya; Maharsipu, Yohannes Gabriel Adven Christy; Purniawan, Agung; Fikri Kurniawan, Muhammad; Tri Wicaksono, Sigit; Ardhyananta, Hosta (IPTEK, DRPM, Institut Teknologi Sepuluh Nopember, 2024)
One of the major concerns associated with the use of silicone material is microorganisms and fungal growth which can result in degradation of the material, inflammation, and chronic infection. Thus, the development of antimicrobial silicone elastomer is becoming necessary. The aim of this study was to evaluate the effect of adding different concentrations of chitosan particles into the silicone matrix. The samples were characterized using a Universal Testing Machine (UTM), Scanning Electron Microscopy (SEM), MTT Assay, antibacterial and hydrolytic material degradation for a month. The addition of 50% chitosan recorded the highest value in the pore area of 29.282 with the widest zone of bacterial inhibition of 6.4 ± 0.4 mm as well as the highest% cell viability of 80.08 ± 1.21%, the furthermore, the shortest lifetime predicted from biodegradation test was around 36 weeks.